Extracorporeal shockwave therapy and therapeutic exercise for supraspinatus and biceps tendinopathies in 29 dogs. (15th October 2016) - Leeman, J. J.; Shaw, K. K.; Mison, M. B.; Perry, J. A.; Carr, A.; Shultz, R.
Abstract : Supraspinatus tendinopathy (ST) and biceps tendinopathy (BT) are common causes of forelimb lameness in large‐breed dogs and have historically been treated with conservative management or surgery. Extracorporeal shockwave therapy (ESWT) and therapeutic exercise (TE) are thought to be treatment options for these conditions. The objectives of this study were to report the clinical presentations of dogs treated with ESWT for shoulder tendinopathies, to determine the association between shoulder lesion severity identified on ultrasonography or MRI and outcome, and to compare the outcomes of dogs treated with ESWT with and without TE. Medical records of 29 dogs diagnosed with shoulder tendinopathies and treated with ESWT were reviewed, and 24 dogs were diagnosed with either unilateral BT or BT and ST. None were found to have unilateral ST. Five dogs were diagnosed with bilateral disease. Eighty‐five per cent of dogs had good or excellent outcomes determined by owner assessment 11–220 weeks after therapy. Outcomes were found to be better as tendon lesion severity increased (P=0.0497), regardless if ESWT was performed with or without TE (P=0.92). ESWT should be considered a safe primary therapeutic option for canine shoulder tendinopathies. Larger controlled prospective studies are needed to adequately assess these findings.